Identification of the insertion site of transgenic DNA based on cyclization of the target gene with the flanking sequence and nested inverse PCR - Jiayu Wang; Xuetong Bi; Wei Chen; Qinyue Zhao; Jinqi Yang; Xiangjun Tong; Meiping Zhao (Talanta Open, 2021)
We demonstrate a novel method for identification of the insertion site of transgenic DNA by construction a circular DNA containing part of the transgenic DNA (tDNA) and its flanking sequence, which would be different from those in the native genomic DNA (gDNA). Using follistatin (FST) as a model of tDNA, we cleaved the sequence of FST gene and the adjacent sequence with a proper combination of restriction endonuclease and nicking endonuclease and isolated the resultant fragments containing the target FST gene from the gDNA background. Two types of previously unknown ligation property of T7 DNA ligase were disclosed in our experiments. One is non-templated single-stranded overhang ligation capability; the other one is the successful ligation of 3’-overhang and 5’-recessed ends in the presence of two mismatched base pairs. By virtue of these efficient ligation reactions, we successfully construct the circular DNA with high cyclization yield. Further coupling with nested inverse PCR, the method enabled identification of transgenic follistatin a (fsta) cDNA in zebrafish embryonic DNA. The established method provides a practical tool to determine the insertion site of tDNA with a sensitivity of 103 copies in 1.0 μg of gDNA and high specificity. It may be further extended for gene doping detection and assessment of the safety of gene therapy and genetically modified organisms.